2017
DOI: 10.1007/s11948-017-9900-8
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Medical Education: A Cross Sectional Study on a Developing Country’s Perspective

Abstract: To determine the attitude of general practitioners towards continuing medical education (CME) and reasons motivating or hindering them from attending CME procedures, we conducted a cross-sectional survey from November 2013 to April 2014 in Karachi. Three hundred general practitioners who possessed a medical license for practice in Pakistan filled a pre-designed questionnaire consisting of questions pertaining to attitudes towards CME. Data was entered and analyzed using SPSS v16.0. 70.3% (n = 211) of the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This finding has been confirmed across national and international studies [30], and indeed little has changed in the past two decades, as a study in the same region some 20 years ago revealed that physicians had little time allocated for CME practice [31]. Time constraints were the second most common reason for not attending CME activities in a Pakistani sample of physicians [32].…”
Section: Resultsmentioning
confidence: 61%
“…This finding has been confirmed across national and international studies [30], and indeed little has changed in the past two decades, as a study in the same region some 20 years ago revealed that physicians had little time allocated for CME practice [31]. Time constraints were the second most common reason for not attending CME activities in a Pakistani sample of physicians [32].…”
Section: Resultsmentioning
confidence: 61%
“…This nding has been con rmed across national and international studies [32], and indeed little has changed in the past two decades, as a study in the same region some 20 years ago revealed that physicians had little time allocated for CME practice [33]. Time constraints were the second most common reason for not attending CME activities in a Pakistani sample of physicians [34]. The problem of a lack of protected time, we suspect, must have increased in recent times.…”
Section: Resultsmentioning
confidence: 73%
“…This finding has been confirmed across national and international studies [21], and indeed little has changed in the past two decades, as a study in the same region some 20 years ago revealed that physicians had little time allocated for CME practice [22]. Time constraints were the second most common reason for not attending CME activities in a Pakistani sample of physicians [23].…”
mentioning
confidence: 61%